Cardiac findings in children with juvenile Dermatomyositis at disease presentation - Serdar Cantez; Gil J. Gross; Ian MacLusky; Brian M. Feldman (BMC, 2017)
Abstract Background Juvenile Dermatomyositis (JDM) is a pediatric vasculopathy characterized primarily by skin and muscle involvement. Cardiac findings have been reported in children with JDM but have rarely been investigated in detail. Methods We aimed to describe the relevant clinical and laboratory cardiac findings of a cohort of patients with JDM, followed at one centre, at disease diagnosis. Results We performed a retrospective review of 105 patients with JDM, followed from 1991 to 2007. Six of 70 patients (9%, 6% of the entire cohort) had abnormal electrocardiographic (ECG) findings, while 26 of 54 patients (48%, 25% of the entire cohort) had abnormal echocardiographic (echo) findings. Many of these findings were either mild or unlikely to be a result of JDM. Conclusions Our findings suggest that cardiac abnormalities at JDM disease onset are frequently seen, but are rarely significant findings due to disease; however, JDM patients should be considered for screening for cardiac disease as late cardiac complications are well recognized.